QRIS SEBAGAI ALAT PENINGKATAN EFISIENSI TRANSAKSI UMKM: STUDI KASUS PERSPEKTIF MASLAHAH EKONOMI DI SEKTOR RITEL - Nurul Wulandari Putri; Anton Bawono (Cahaya Ilmu Bangsa, 2025)
QRIS is a barcode-based digital payment system designed to facilitate cashless transactions. This study aims to analyze the impact of QRIS implementation on the efficiency of UMKM transactions and the challenges faced in an Islamic economic perspective. The research method used is qualitative, with interviews conducted with 10 food and beverage UMKM and 10 consumers. The results show that the implementation of QRIS has a significant positive impact on increasing the efficiency of micro, small and medium enterprises transactions through accelerating the digital payment process and increasing business competitiveness. However, the dominance of cash payments, low digital literacy among MSMEs, and less supportive ICT infrastructure are the main challenges. It is recommended to optimize the socialization of QRIS and develop information and communication technology infrastructure so that the benefits of fast transactions can be felt evenly by UMKM while still observing sharia principles.